A Mixed-Methods Evaluation of a Social Paediatrics Block Rotation for Paediatric Residents. (1st June 2016) - Hunter, A; Kay, S; Parker, K; Delahunty-Pike, A; Wahi, G
Abstract: BACKGROUND: Poverty and social injustice have a direct link to health outcomes and health care utilization, especially for children. Understanding the complexity of impact of social determinants on health is essential in providing effective, compassionate care to vulnerable populations. Currently, there is a paucity of literature on the impact of various models of advocacy curricula on pediatric residents and future involvement in advocacy. Social Pediatrics is an approach to child health that focuses on the child, in illness, and in health, within the context of their society, environment, school, and family. OBJECTIVES: 1) To determine if a social pediatrics rotation greater enables residents to become involved in advocacy projects during their residency and interest for career. 2) To identify resident knowledge translation of the social determinants of health and their impact on the pediatric population. 3) To characterize the barriers and enablers, if any, for residents to engage in advocacy. DESIGN/METHODS: The Social Pediatrics rotation was embedded in the second year of a postgraduate pediatric curriculum. Knowledge and attitudes of resident participants before and after the rotation was assessed with written tests and surveys. A qualitative descriptive study of community partners and resident perspectives was semi-structured interviews, thematic coding and analysis via an inductive-iterative approach. RESULTS: 21 residents completed pre-and post- written knowledge tests, and 12 residents completed optional attitudinal surveys. Knowledge increased from 68% prior to rotation, to 80% (p < 0.001) following the rotation. All residents completing written surveys indicated increased likelihood of participating in social pediatrics and advocacy in practice following this rotation. Results from 6 resident and 5 community partner interviews included: enhanced knowledge of social determinants of health, residency curricula development with further mental health placements, future practice models involving vulnerable populations, multi-disciplinary learning opportunities, and advocacy projects both at the patient and community level. Community partners shared experiences of residents demonstrating enthusiasm and engagement in placements, some logistical challenges but value in experiences outside hospital environment, particularly in learning from multidisciplinary team. CONCLUSION: Pediatric residents demonstrate increase in knowledge of social determinants of health and an increased interest in community advocacy initiatives and vulnerable populations following a block rotation in Social Pediatrics. Community partners valued engagement with pediat-ric residents, identifying key learning opportunities in these unique environments and report few barriers to continued involvement. Future directions include impact on advocacy work or career decisions, and multi-centre collaboration.